Comparison of manual versus sonic and ultrasonic toothbrushes: a review - MR Costa (Journal compilation 2007 Blackwell Munksgaard, 2007)
This review of the literature intends to evaluate the effect of brushes with high frequency motion when compared with manual toothbrushes regarding the indices of plaque and gingival bleeding.